Papillomaviruses and HPV vaccination to prevent cervical cancer and other HPV-associated diseases - Lowy, Douglas (Henry Stewart Talks, 2007)
Cervical cancer is attributable to multiple HPV types; HPV16 predominates, Cervical cancer: time line of cervical HPV infections, progression and natural history, Key features of HPV pathogenesis, Challenges to development of a preventive HPV vaccine, A prophylactic vaccine, Formation of papillomavirus virions, Two distinct HPV VLP vaccines are under commercial development, Partial crossprotection against incident infection by other high risk HPV types, Overall efficacy in preventing HPV cervical disease attributable to incident infection, HPV life cycle, How could IM injection of a VLP vaccine prevent mucosal or cutaneous infection at the cervix?, Outstanding medical issues, Regulatory status of HPV VLP vaccines, Pap smear screening without vaccination would prevent more cervical cancer deaths than HPV16/18 vaccination without pap screening, Limitations of current VLP vaccines
Archived at 2018/09/26